Ga(y)mer Theory: Queer Modding as Resistance. - Lauteria, Evan W. (Reconstruction: Studies in Contemporary Culture, 2012)
In the mid-20th century, scholars Johan Huizinga and Roger Caillois positioned play as a pre-civilized human activity that is resistant to capitalism and rationalization. McKenzie Wark extends a theory relationship between play and resistance to contemporary global capitalism in Gamer Theory, a critical theory of games that rests on the gamer standpoint. Gamers are most capable of bearing witness to the injustices of the social realm in contrast to the "fair" structures of game worlds. However, video games as formal rule structures are embedded with ideological forces, products themselves of capitalist enterprise, and video game simulations are powerful normative or normalizing processes. In this paper, I grapple with this uneasy relationship between gamers' resistant play and the normalizing games in which that play occurs. By drawing attention to the intersections of global capitalism, sexuality, and gender, I employ my own experiences with Persona 4 as a case study in which a game deploys normalizing power through its mechanics. In turn, I echo a political commitment to resistant play and look at gaymers' modding practices as a current site of resistance, oriented to the construction of spaces that permit play against normalizing sexual and gender structures. I argue that Gamer Theory's gamer standpoint indeed holds important political salience, but an intersectional approach - in this case practiced through directed attention to "gaymers" - extends resistance to include both "free" play and, importantly, the construction of spaces in which that play occurs.